2014
DOI: 10.1021/am504407n
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Spatial Distribution of Integrin β1 in Patterned Human Mesenchymal Stem Cells Using Super-Resolution Imaging

Abstract: Lineage commitment of human mesenchymal stem cells (hMSCs) could be directed through micro/nanopatterning of the extracellular matrix (ECM) between cells and substrate. Integrin receptors, integrator of the ECM and cell cytoskeleton, function as molecular bridges linking cells to different biophysical cues translated from patterned ECM. Here we report the distinct recruitment of active integrin β1 (ITG-β1) in hMSCs when they were committed toward the cardiomyogenic lineage on a micropatterned surface. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 46 publications
4
15
0
Order By: Relevance
“…Previous studies have illustrated the role of elongated FAs in cardiomyogenic differentiation of cells . In addition, we investigated the dominant role of elongated ITG‐β 1 FA in myocardial lineage commitment of similar patterned hMSCs . Thus, based on previous findings and our current observations we postulated that micropatterning promoted the formation of elongated ITG‐β 1 FA which in turn induced the development of aligned actomyosin stress fibers without crosslinking.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Previous studies have illustrated the role of elongated FAs in cardiomyogenic differentiation of cells . In addition, we investigated the dominant role of elongated ITG‐β 1 FA in myocardial lineage commitment of similar patterned hMSCs . Thus, based on previous findings and our current observations we postulated that micropatterning promoted the formation of elongated ITG‐β 1 FA which in turn induced the development of aligned actomyosin stress fibers without crosslinking.…”
Section: Discussionsupporting
confidence: 56%
“…Recently, we showed that active ITG‐β 1 FAs were predominantly expressed in hMSCs cultured on fibronectin coated substrates as compared to other types of ITG‐β . In addition, in another study, it was observed that ITG‐β 1 activation through increased fibronectin density enhanced the cell traction forces .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Cell micropatterning was performed as previously described [22] . Briefly, polydimethylsiloxane (PDMS) elastomeric patterned stamps bearing 20 µm elevated lanes and 40 µm spacing were fabricated and utilized to ink the human plasma derived fibronectin (BD Biosciences) onto glutaraldehyde (Sigma) treated cover glasses [18] .…”
Section: Methodsmentioning
confidence: 99%
“…Most of them involve the contact of a stamp or a writing head with a substrate . In spite of their merits, they all lead to significant drawbacks in terms of repeatability, resolution, and costs . Conversely, the droplet‐based techniques involve contact‐free procedures and offer several advantages in terms of simplicity, versatility, and control of deposition .…”
Section: Introductionmentioning
confidence: 99%